Colonial Anxiety Through Literary Signifier - Teggin, Edward Owen (Humanis; Vol 25 No 4 (2021), 2021)
This article seeks to broaden the ongoing debate surrounding the nature and structure of colonial anxiety by incorporating elements of literary discussion into the conversation. It is a commonly experienced problem that the current definition of colonial anxiety is not mutable, and is often viewed as a singular indivisible whole. This, of course, cannot be the case due to the inherent links between anxiety generally, and its sub-set “colonial anxiety”. Whilst there are many methods of examining colonial anxiety, the current study seeks to examine the problem through literature. The investigation will examine George Orwell’s Burmese Days and Multatuli’s Max Havelaar as core texts. Whilst Orwell’s anti-imperial feelings have been well publicized, as has Multatuli’s anti-colonial standpoint, the notion that they were individual colonial servants who likely, it is argued, suffered from colonial anxiety, has not. Also crucial to the discussion will be the attempt to more fully integrate diverse regions such as Burma and Indonesia into the wider debate on colonial anxiety.